Kewenangan PTUN dalam Mengadili Perbuatan Melanggar Hukum Oleh Badan dan/atau Pejabat Pemerintahan Onrechtmatige Overheidsdaad (OOD) - Andy Noor Januar Rizky Rizky; Anis Rifai (Jurnal Bedah Hukum, 2026)
The background of this research departs from a significant change in the authority of the State Administrative Court after the enactment of the Government Administration Law and PERMA Number 2 of 2019, which opens up space for testing the government's factual actions as part of administrative disputes. This change raises problems regarding the limits of the new authority of the State Administrative Court and how it is applied in cases of Unlawful Acts by Agencies and/or Government Officials. The purpose of this paper is to analyze the scope of the PTUN's authority in handling OOD cases and to examine its application through court decisions. This study uses normative legal methods with a legislative approach and qualitative analysis of primary, secondary, and related legal materials. The results of the study show that PERMA Number 2 of 2019 expressly stipulates that OOD cases are the absolute authority of the PTUN so that the settlement is no longer in the civil regime. The examination of the government's factual actions now uses the touchstone of administrative law and the general principles of good governance. This finding is strengthened through the analysis of Decision Number 315/G/TF/2022/PTUN. JKT and Decision Number 230/G/TF/2019/PTUN. JKT assesses that the factual actions of government officials cause losses to the community. From these results, it is concluded that the expansion of the authority of the PTUN provides a more appropriate legal protection mechanism for citizens and strengthens the principle of government accountability within the framework of the state of law.